Diet‐wide association study of 92 foods and nutrients and lung cancer risk in the European Prospective Investigation into Cancer and Nutrition study and the Netherlands Cohort Study. Issue 11 (4th August 2022) - Heath, Alicia K.; Muller, David C.; van den Brandt, Piet A.; Critselis, Elena; Gunter, Marc; Vineis, Paolo; Weiderpass, Elisabete; Boeing, Heiner; Ferrari, Pietro; Merritt, Melissa A.; Rostgaard‐Hansen, Agnetha L.; Tjønneland, Anne; et al.
Abstract: It is unclear whether diet, and in particular certain foods or nutrients, are associated with lung cancer risk. We assessed associations of 92 dietary factors with lung cancer risk in 327 790 participants in the European Prospective Investigation into Cancer and Nutrition (EPIC). Cox regression yielded adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) per SD higher intake/day of each food/nutrient. Correction for multiple comparisons was performed using the false discovery rate and identified associations were evaluated in the Netherlands Cohort Study (NLCS). In EPIC, 2420 incident lung cancer cases were identified during a median of 15 years of follow‐up. Higher intakes of fibre (HR per 1 SD higher intake/day = 0.91, 95% CI 0.87‐0.96), fruit (HR = 0.91, 95% CI 0.86‐0.96) and vitamin C (HR = 0.91, 95% CI 0.86‐0.96) were associated with a lower risk of lung cancer, whereas offal (HR = 1.08, 95% CI 1.03‐1.14), retinol (HR = 1.06, 95% CI 1.03‐1.10) and beer/cider (HR = 1.04, 95% CI 1.02‐1.07) intakes were positively associated with lung cancer risk. Associations did not differ by sex and there was less evidence for associations among never smokers. None of the six associations with overall lung cancer risk identified in EPIC were replicated in the NLCS (2861 cases), however in analyses of histological subtypes, inverse associations of fruit and vitamin C with squamous cell carcinoma were replicated in the NLCS. Overall, there is little evidence that intakes of specific foods and nutrients play a major role in primary lung cancer risk, but fruit and vitamin C intakes seem to be inversely associated with squamous cell lung cancer. Abstract : What's new? Lung cancer is the leading cause of cancer death worldwide, and while smoking is the most significant factor affecting lung cancer risk, other environmental and genetic factors may contribute. Here, the authors looked for an association between the foods people eat and their lung cancer risk. Using an approach they call a diet‐wide association study, modelled after genome‐wide association studies, they evaluated 92 individual food and nutrient intakes for association with lung cancer risk. No major associations were detected for lung cancer overall, but higher fruit and vitamin C intakes were associated with lower squamous cell lung cancer risk.